Improving mechanical and electrical properties of Cu/SAC305/Cu solder joints under electromigration by using Ni nanoparticles doped flux - Bashir, Muhammad Nasir; Haseeb, A.S. Md. Abdul (Springer, 2018)
The electromigration (EM) degrades the structural, mechanical and electrical properties of solder joints. An effort has been made to investigate the effects of the Ni nanoparticles (NP) doped flux on the mechanical properties and electrical resistance of SAC305 solder joints subjected to EM. SAC305 solder joints were prepared using NP-doped flux. A current density of 3 × 103 A/cm2 was applied to the joints at a constant temperature of 150 °C. Tensile tests were performed before and after the EM tests. Results reveal that after the addition of Ni NP-doped flux, the mechanical strength improved before and after EM. After EM, the fracture path for doped solder joint did not migrate to the cathode side as compared to un-doped solder. Ni NP also improved the electrical resistance and lifetime of the solder joint. The use of Ni NP-doped flux thus minimized the effects of EM and improved the mechanical and electrical performance of the solder joints.